2021
DOI: 10.2147/cia.s343057
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Study of Isocaloric Different Dietary Patterns on the Life Span in Healthy Population

Abstract: How to prolong life by diet has been widely concerned. There are many reports about the effects of different dietary patterns on life span, but the results are not consistent. The main reason may be that total energy intake has not been considered. This study aims to explore the effects of isocaloric different dietary patterns on population life span. Materials and Methods: From the data of the follow-up population, eligible participators were divided into normal control (NC) group (28.31% fat, 12.37% protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, our finding suggests that the above four up-regulated bile acids may be beneficial to healthy aging. Notably, Zhang et al found that the level of glycocholic acid was significantly decreased with age ranging from 20 to 74 years old [ 22 ]. In turn to see the discovery of this study, it is reasonably speculated that the bile acids metabolism of the healthy centenarians may revert to a more youthful state with respect to the elderly people aged 60–70 years, which also represents the unique metabolic signatures of the healthy centenarians from the longevous region, and a path to health and longevity by means of appropriately up-regulated bile acids metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our finding suggests that the above four up-regulated bile acids may be beneficial to healthy aging. Notably, Zhang et al found that the level of glycocholic acid was significantly decreased with age ranging from 20 to 74 years old [ 22 ]. In turn to see the discovery of this study, it is reasonably speculated that the bile acids metabolism of the healthy centenarians may revert to a more youthful state with respect to the elderly people aged 60–70 years, which also represents the unique metabolic signatures of the healthy centenarians from the longevous region, and a path to health and longevity by means of appropriately up-regulated bile acids metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[29] In people, serum levels of succinate rise with age. [119] From one perspective, then, a rise in succinate, as an adaptation to hypoxia, is a biochemical example of allostasis, a distortion from optimal homeostasis for the purpose of meeting an environmental pressure. [120] However, hypoxia in the right amount is also hormetic-a moderate challenge that strengthens the organism.…”
Section: Succinate Hypoxic Signaling and Oxidative Stressmentioning
confidence: 99%